The Urgency of Legal Harmonization in Waqf Land Certification Practices: Tasikmalaya City Case Study - Acep Zoni Saeful Mubarok; Cecep Soleh Kurniawan; Pepep Puad Muslim (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
The main problem with waqf land is its lack of formal legal status, as evidenced by the absence of a certificate. To provide legal certainty, the government issued a series of regulations that support the direction of waqf assets, ensuring they are guaranteed and legally maintained. However, in practice, their regulations have become fragmented, leading to overlapping regulations and a lack of synchronisation in institutional procedures. This condition is evident in the city of Tasikmalaya, where there is a data error and the name exchange between Wakif and Nazhir due to the lack of harmonization of regulations. This study aims to analyze the urgency of harmonizing regulations governing waqf land certification to achieve legal certainty and data accuracy. The approach used is a qualitative-normative case study design in Tasikmalaya City. Data was collected through document review, in-depth interviews, and field observations. The results of the study show that there is still disharmony and asynchrony between the practice of implementing waqf laws and regulations and other rules, such as those from ATR/BPN, BWI, and the Ministry of Religion. The implications of this study highlight the importance of establishing an integrated legal framework to prevent administrative errors and improve legal coordination and harmonization in the practice of waqf land certification. The contribution of this research lies in providing a normative basis for waqf regulatory governance reform in Indonesia.